Optimization Of Eurycomanone Yield Using Response Surface Methodology By Water Extraction - He, Yu Hai; Ahmad Ziad, Sulaiman (2015)
Nutraceuticals and phytomedicines are largely used in pharmaceutical industry at this era. Phytomedicines are pharmaceuticals which made from plants which has significant property of treating some illnesses. Tongkat Ali, or eurycoma longifolia, is a traditional herb medicine used as aphrodisiac, general tonic, anti-Malaria, and anti-Pyreti. Nowadays, Tongkat Ali has become known globally due to its ability to treat erectile dysfunction (ED) and to improve sexual desire. Eurycomanon is a very important quassinoids found in Tongkat Ali extract which has a potential to be developed as complementary for anti-cancer therapy. In this research, extraction of eurycomanone from tongkat ali was performed according response surface methodology. Optimization of eurycomanone yield was obtained through central composite design (CCD). The maximum eurycomanone amount which is 0.559% was obtained at solvent to raw material ratio of 28.8:1 g/g, duration of extraction of 3 hour, and 0.054-0.154 mm of raw material.